Responsible CSR Communications: Avoid “Washing” Your Corporate Social Responsibility (CSR) Reports and Messages (Journal of Leadership, Accountability and Ethics, 2021)
With the rise of Corporate Social Responsibility (CSR) reporting, questions have emerged regarding its true utility; CSR reports may more closely resemble marketing materials than financial statements as much of the data companies provide can be cherry picked. For example in 2011, only 20% of S&P 500 companies published CSR reports vs 85% in 2017 and 90% in 2019.Why is this relevant for communicators? Because the responsibility of producing and promoting CSR reports very often falls under the responsibility of the corporate communications team. How to avoid "CSR-washing" and all the other “washing” incidents – green-washing, blue-washing, rainbow-washing, vegan-washing,...? How to focus on portraying the organization as a truly and authentic dedicated corporate citizen?In-depth interviews with 15 senior communication practitioners in Canada helped identify what are “authentic” and “responsible” communications in the CSR space: using facts and testimonials, being transparent, showing authenticity as well as demonstrate the clear alignment with the organization’s purpose.
Keywords: leadership accountability, ethics; corporate social responsibility, CSR, greenwashing, authenticity, credibility, sustainability reporting, corporate reputation, corporate communications, stakeholder relationship, corporate citizenship, ESG, purpose